SCAR MARKER DEVELOPMENT FOR THE CORRECT IDENTIFICATION OF IRIS ENSATA - Mughees, Mohd; Jha, Shipra Rani; Ahmad, Javed; Ahmad, Altaf (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of this research was to develop the RAPD based SCAR marker for the correct identification of the Iris ensata Thunb. (I. ensata) plant from its adulterants. Methods: Five samples of I. ensata. from the different geographical area were used in this study. The plant genomic DNA was isolated with the CTAB method with some modification (as dried samples were also used). After that, polymorphism was checked with the help of the 10-mer random primers of OPAA and BG series. Then, the bands of interest were eluted and cloned into pGEMT easy vector for the sequencing. Finally, the sequence is used to develop the SCAR primers (Ir-f andIr-R) specific for I. ensata and the developed primers also validated with respect to the market samples. Results: A putative 580 bp sequence specific for Iris ensata was identified from the randomly amplified polymorphic DNA (RAPD) analysis. To overcome the main limitation of RAPD it has been converted into SCAR markers. So that, this specific band was then eluted, cloned and sequenced. After that, SCAR primers (Ir-F and Ir-R) were synthesized by using this sequence. For the validation of the synthesized SCAR primers, they were tested with respect to the market samples. The amplicon of 260 bp was produced by the SCAR primers in the authentic I. ensata but market samples did not produce any bands with the synthesized SCAR primers. Conclusion: The results of this study show a high level of polymorphism in the RAPD pattern of the different accessions of the plant. Furthermore, this study results in the successful development of the RAPD based SCAR marker for the identification of the I. ensata.